Schottky structures nZnSe(O,Te)/Ni as candidates for selective ultraviolet detectors - Katrunov, K.; Starzhinskiy, N.; Grinyov, B.; Galchinetskii, L.; Bendeberya, G.; Bondarenko, E. (Functional Materials, 2008)
Data on optical and electrophysical properties of photosensitive structures with Schottky barrier of nZnSe(O, Te)/Ni type are presented. The photoreceivers of this type have current sensitivity Sλ = 0.1-0.15 A/W for λ = 420-440 nm, and at λ = 250-270 nm Sλ is 0.02 A/W; the threshold sensitivity is ~10⁻¹² W·cm⁻¹·Hz⁻¹/². For separation of various UV spectrum regions showing photobiological activity, light filters have been developed intended for use thereof in detecting devices.